A set of robust fluorescent peptide probes for quantification of Cu(ii) binding affinities in the micromolar to femtomolar range1. Issue 3 (11th March 2015) - Young, Tessa R.; Wijekoon, Chathuri J. K.; Spyrou, Benjamin; Donnelly, Paul S.; Wedd, Anthony G.; Xiao, Zhiguang
<x xml:space="preserve">Abstract</x> A set of four fluorescent probes were developed and demonstrated to be capable of quantifying Cu(ii) binding affinities in the micromolar to femtomolar range and exploring Cu(ii) binding ligands in peptides and proteins.